Worldwide Examination of Magnetic Responses to Heavy Metal Pollution in Agricultural Soils - Xuanxuan Zhao; Jiaxing Zhang; Ruijun Ma; Hui Luo; Tao Wan; Dongyang Yu; Yuanqian Hong (Agriculture, 2024)
Over the last decade, a large number of studies have been conducted on heavy metals and magnetic susceptibility (<semantics>χlf</semantics>) measurement in soils. Yet, a global understanding of soil contamination and magnetic responses remains elusive due to the limited scope or sampling sites of these studies. Hence, we attempted to explore a pollution proxy on a global scale. Through a meta-analysis of data from 102 published studies, our research aimed to provide a worldwide overview of heavy metal pollution and magnetic responses in agriculture soils. We mapped the geographic distribution of nine heavy metals (Cr, Cu, Zn, Pb, Ni, As, Cd, Mn, and Fe) in agricultural soils and explored their pollution sources and contributions. Since 2011, The accumulation of heavy metals has escalated, with industrial activities (31.5%) being the largest contributor, followed by agricultural inputs (27.1%), atmospheric deposition (22.66%), and natural sources (18.74%). The study reports <semantics>χlf</semantics> ranging from 6.45 × 10−8 m3/kg to 319.23 × 10−8 m3/kg and <semantics>χfd</semantics> from 0.59% and 12.85%, with the majority of the samples being below 6%, indicating heavy metal influence mainly from human activities. Pearson’s correlation and redundancy analysis show significant positive correlations of Pb, Zn, and Cu with <semantics>χlf</semantics> (r = 0.51–0.53) and Mn and Fe with <semantics>χfd</semantics> (r = 0.50–0.53), while Pb, Zn, Cu, and As metals were shown to be key factors of variation in magnetic response. The average heavy metal pollution load index of 2.03 suggests moderate global agricultural soil pollution, with higher heavy metal contamination in areas of high <semantics>χlf</semantics>. Regression analysis confirms soil is considered to be non-polluted below <semantics>χlf</semantics> of <semantics>26×10−8 m3/kg</semantics> and polluted above this threshold, with all contamination factors of metals showing a linear correlation with <semantics>χlf</semantics> (R = 0.72), indicating that a significant relationship between <semantics>χlf</semantics> and the geochemical properties of soils continues to exist on a global scale. This study provides new insights for large-scale agricultural soil quality assessment and magnetic response.